Fracture Resistance of Residually-Stressed Ceramic Laminated Structures - Gogotsi, G.A.; Lugovoi, N.I.; Slyunyaev, V.N. (Проблемы прочности, 2004)
We have studied the effect of residual stresses on fracture resistance and crack arrest behavior of asymmetric ceramic laminated Si3N4 /Si3N4 -TiN structures. Using a compliance method, we assessed is the technique of R-curve construction for laminar composites. For laminar structures with layers varying by their elastic characteristics we developed an analytical method for calculation of “fracture resistance - crack length” dependence. The method applicability is verified by calculation of stress intensity factors for laminar specimens with edge crack. The calculated results are compared to the experimental data.